The Limits of Working with Children Cards in Protecting Children - Budiselik, William; Crawford, Frances; Squelch, Joan (Routledge, 2009)
In 2006 Western Australia passed legislation that introduced a system to check criminalrecords and issue permits to those who wish to work with children. In 2007, thelegislation was described by the minister responsible as a ‘‘powerful system that wouldprevent harm to children’’. This paper explores that system and identifies limits to itseffectiveness. The paper concluded that unless the system’s limits are fully appreciatedthere is a possibility of a paradoxical outcome, whereby children’s lives will be less safe. Italso raises the question of whether in the area of record checking a national approach is not preferable to each state and territory developing its own system.